Effect of Thermal Processing on Color, Phenolic Compounds, and Antioxidant Activity of Faba Bean (Vicia faba L.) Leaves and Seeds - Shu-Cheng Duan; Soon-Jae Kwon; Seok-Hyun Eom (MDPI AG, 2021)
The leaves and seeds of the faba bean are good sources of L-3,4-dihydroxyphenylalanin (L-dopa), and are usually eaten with thermal cooking methods. However, little information is available on the effect of thermal treatments on their nutritional value. We compared the changes in color, contents of L-dopa, vitamin C (Vc), total phenolics (TP), total flavonoids (TF) and antioxidant activity after dry heating or steaming faba bean leaves and seeds. The young leaves provided higher values of all the estimate factors, regardless of the thermal treatment. Steaming significantly degraded nutritional values of the leaves, but less changed in seeds, whereas dry heat maintained these attributes. The contents of L-dopa, Vc, TP and TF were shown to have strongly positive correlations with antioxidant activity in the leaves, whereas only L-dopa content was positively correlated with antioxidant activity of the seeds. Faba leaves contained relatively high L-dopa which possessed strong antioxidant activity compared to the Vc. As L-dopa is an important contributor to the antioxidant activity of faba leaves and seeds, consuming L-dopa from leaves may provide beneficial effects not only regarding Parkinson's Disease.